2015
DOI: 10.1164/rccm.201502-0223oc
|View full text |Cite
|
Sign up to set email alerts
|

Host Response to the Lung Microbiome in Chronic Obstructive Pulmonary Disease

Abstract: Rationale: The relatively sparse but diverse microbiome in human lungs may become less diverse in chronic obstructive pulmonary disease (COPD). This article examines the relationship of this microbiome to emphysematous tissue destruction, number of terminal bronchioles, infiltrating inflammatory cells, and host gene expression. Measurements and Main Results: Ten operational taxonomic units (OTUs) was found sufficient to discriminate between control and GOLD stage 4 lung tissue, which included known pathogens s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(176 citation statements)
references
References 33 publications
7
162
2
5
Order By: Relevance
“…Кроме того, известно о росте Lactobacillus, которые более представлены у больных с тяжелой БА, а также в микробиоте легочной ткани, взятой во время транс-плантации легких у больных крайне тяжелой ХОБЛ [24]. И, наконец, стоит отметить более выраженное присут-ствие бактерий рода Alloiococcus у больных тяжелой БА по сравнению с легкой.…”
Section: обсуждение основного результата исследованияunclassified
“…Кроме того, известно о росте Lactobacillus, которые более представлены у больных с тяжелой БА, а также в микробиоте легочной ткани, взятой во время транс-плантации легких у больных крайне тяжелой ХОБЛ [24]. И, наконец, стоит отметить более выраженное присут-ствие бактерий рода Alloiococcus у больных тяжелой БА по сравнению с легкой.…”
Section: обсуждение основного результата исследованияunclassified
“…The analysis of the bacterial microbiota in COPD lung tissue confirmed that there was a significant difference in composition of the bacterial community between COPD and health lungs [42,43]. The lungs of patients with very severe COPD contained a different community of bacteria to those of controls.…”
Section: Copdmentioning
confidence: 76%
“…Recently, Sze and colleagues 34 have found not only that analysis of the microbiome can be used to discriminate between control and severe COPD lung tissue, but they also demonstrated that a decline in microbial diversity correlated with emphysematous lung destruction, airway remodeling, and CD4 T-cell lymphocyte accumulation within the lung.…”
Section: Disruption Of Homeostatic Maintenance and Repair Systemmentioning
confidence: 99%